Single dimension-based fuzzy sliding mode control design for the stabilisation of underactuated unmanned underwater vehicle - Mustafa Abro, G.E. (Inderscience Publishers, 2021)
The paper provides the comparative analysis of traditional fuzzy-based sliding mode controller (F-SMC) and single dimension-based fuzzy sliding mode controller (SDF-SMC) for the stabilisation of an underactuated unmanned underwater vehicle (UUV). It has been observed that the sliding mode control design stabilises the underactuated mechatronic system very smartly, but it causes a high number of oscillations known as Zeno phenomenon. This effect can easily be eliminated using fuzzy version of sliding mode controller (F-SMC) but at the same moment it takes high processing time due to fuzzification, inference and then defuzzification steps. The major reason for consuming such a huge process time is the two-dimensional rule base table. Thus, this research work will turn that two-dimensional table of rules into single dimension and propose single input-based fuzzy sliding mode controller (SDF-SMC) generating crisp input. In addition, this paper presents the comparative simulation work between conventional fuzzy-based SMC (F-SMC) and single dimension-based fuzzy SMC (SDF-SMC), carried on MATLAB/Simulink software to reduce the process time. In order to validate the effectiveness of proposed control scheme, the SDF-SMC algorithm is also implemented using proper hardware and experimental setup. Copyright Â© 2021 Inderscience Enterprises Ltd.